Application of CBT in Coping with Compulsive Buying on Online Shopping by Young Adult Woman - Teguh Lesmana; Samsunuwiyati Mar’at; Widya Risnawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2017)
The purpose of this study is want to know how the results of cognitive behavior therapy (CBT) application in coping with compulsive buying on online shopping by young adult woman. Compulsive buying is defined as buying behavior done by individual repetitively, happens automatically as response toward inner state or certain events. The buying behavior which often done tend to be excessive until finally cause problem in life. CBT is a psychological intervention which handle the interaction among how people thinks, feels and behaves. Online shopping is a process of buying goods or services from someone who sell through internet. The number of samples in this study consist of 113 young women with age between 20 to 30 years old which obtained from online questionnaires. From 113 subjects, it is found that there are 5 people with high level of compulsive buying and doing online shopping several times a week. In the process, only 2 people remains who are willing to continue through until the intervention started. This study used one-group pretest-posttest design, which measure compulsive buying among participants by using compulsive buying scale (CBS). After the participants are given manipulation with CBT, then there will be remeasurement towards compulsive buying using CBS again. According to the results of intervention, it is known that CBT can reduce the frequency of online shopping both subjects and reduce the level of compulsive buying tendency according to CBS. Factors which supports change are good cooperation from the subjects and motivation to change. Key Words: CBT, compulsive buying, online shopping